MENINGKATKAN KEMAMPUAN MEMBACA KATA BENDA BAGI ANAK TUNAGRAHITA RINGAN - Jumiati - Intan (Jurnal Penelitian Pendidikan Khusus, 2012)
This study, using experimental approaches in the form of Single Subject Research (SSR). As the subject is one child mild mental retardation. Assessment conducted in this study, consistent in how children actually answer the question of the ability of existing early childhood. This study first examines the baseline condition, children have the ability to read, then given intervention by using the flipchart Having given intervention, researchers measured back reading skills possessed noun child. Data obtained through direct observation, and analysis of data. Data analysis in this research is the data visually in the form of graphs.